Dorsoventral lineage restriction in wing imaginal discs requires Notch. - Micchelli, C.A.; Blair, S.S. (Nature, 1999)
The formation of boundaries that prevent the intermixing of cells is an important developmental patterning mechanism. The compartmental lineage restrictions that appear in the developing imaginal discs of Drosophila are striking examples of such boundaries. However, little is known about the cellular mechanism underlying compartmental lineage restrictions. The dorsoventral (D/V) lineage restriction that arises late in the developing wing imaginal disc requires the dorsal expression of the transcription factor Apterous and it has been hypothesized that apterous (ap) maintains compartmentalization by directly regulating the expression of molecules that modify cell adhesion or affinity. However, ap expression also regulates signalling between dorsal and ventral compartments, resulting in high levels of Notch signalling at the D/V boundary. Here we show that the formation of Notch-dependent boundary cells is required for the D/V lineage restriction.